Pain Management in Endodontics: a Narrative Review of Analgesic Use Preoperative, Intraoperative, and Postoperative - Tomizioli, N.; Beccherle, M.; Zangani, A.; Bertajola, A.; Colapinto, G.; Cordioli, N.; Gualtieri, M.; Balliu, F.; Belviglieri, L.; Montagna, P.; Faccioni, P.; Albanese, M. (Journal of applied cosmetology, 2025)
Pain management in endodontics is a critical aspect of dental care, as the fear of endodontic pain often influences patient behavior and treatment outcomes. This narrative review examines the mechanisms, classification, and management strategies for pain associated with endodontic procedures, focusing on preoperative, intraoperative, and postoperative stages. Preoperative pain, often caused by irreversible pulpitis or periapical infections, is exacerbated by inflammatory mediators like prostaglandins, which lower pain thresholds and hinder anesthetic efficacy. Intraoperative pain arises from difficulties in achieving adequate anesthesia, particularly in cases of pulpitis, while postoperative pain, peaking within 24 hours, is linked to inflammatory responses in periapical tissues. A range of pharmacological options is discussed, including NSAIDs, paracetamol, corticosteroids, and opioids, alongside their mechanisms of action, efficacy, and side effects. NSAIDs remain the first-line treatment due to their anti-inflammatory and analgesic properties, with ibuprofen demonstrating rapid and effective pain relief. Corticosteroids are highlighted for their ability to enhance anesthetic success and reduce inflammation, particularly in severe cases. Opioids and gabapentinoids are reserved for more severe or neuropathic pain, with cautious use due to potential dependency risks. The aim of this review is to emphasize the importance of tailored analgesic strategies that address the specific pain phase, patient characteristics, and procedural requirements. This comprehensive approach not only alleviates pain but also enhances the overall effectiveness of endodontic treatment, ensuring better patient outcomes and satisfaction.